Penerapan Model Pembelajaran PBL dalam Mata Pelajaran Informatika Kelas X 5 untuk Meningkatkan Kreativitas Siswa di SMA Negeri 8 Maros - Salsabilah Muslim; Nuramira Nuramira; Nasir Nasir (Jurnal Budi Pekerti Agama Islam, 2024)
In an era of cultural acceleration and rapid advancements in science and technology, this research evaluates the application of the Problem-Based Learning (PBL) model in Informatics at SMA Negeri 8 Maros, focusing on enhancing student creativity. Employing a quantitative method within the Classroom Action Research framework, this study involves cycles of planning, action, observation, and reflection. Data collected through creativity tests, surveys, and class observations reveal that PBL significantly boosts student creativity. These findings are crucial, considering the critical role of education in preparing future generations for digital era challenges. This study highlights how education, especially in Informatics covering programming, artificial intelligence, and computer networking, can adapt to changing times. By integrating technology and innovative approaches into the learning process, students can enhance creativity and other essential skills needed in the digital age. This research offers valuable insights for educators and policymakers in preparing students for a bright, sustainable future.